Етнічна приналежність похованих у плитових могилах римського часу в Південно-Західному Криму у зв'язку з проникненням сарматів на територію сучасної України - Піоро, І.С. (Археологія, 2002)
На основі вивчення конструкції могил пізньоантичних некрополів Південно-Західного Криму, особливостей поховального обряду речей заупокійного вжитку та їх порівнянню з археологічними пам'ятками інших територій Південно-Східної Європи аргументовано гіпотезу про етнічну приналежність плитових могил Північного Причорномор'я аборигенам Північного Кавказу, які були асимільовані сарматами. Погребения, совершенные по обряду трупоположения, при совершении которых использовались каменные плиты, среди прочих разнообразных захоронений находятся в некрополях позднеримского времени Юто-Западного Крыма (в кургане около Братского кладбища, на территории совхоза «Севастопольский», в могильниках Бельбек І, Бельбек ІІ, Терновка ІІ, Инкерманский).
Во всех плитовых могилах зафиксированы основные черты сарматского обряда. В погребальном инвентаре распространены вещи, характерные как для сарматских памятников, так и для северо-западных территорий.
Наличие в некрополях римского времени в различных регионах Юго-Восточной Европы аналогичных плитовых захоронений с подобным погребальным обрядом и инвентарем позволяет предположить миграцию в Северное Причерноморье осармаченных аборигенов Северного Кавказа вместе с другими сармато-аланскими племенами. Обитание сарматов на территории Украины в первые века нашей эры подтверждает их вхождение в состав носителей черняховской культуры. Inhumation burials with stone slabs are situated in the necropolises of the Late Roman period in the South-Western Crimea (in the barrow near the Bratskoe cemetery on the territory of the State farm «Sevastopolsky», in the necropolises Belbek-I. Belbek-II, Теrnovka-II, Inkerman).
In all the slab burials the basic features of the Sarmatian ritual (inhumations, stretched on the back, sometimes with the legs crossed in shanks, wrists on the pelvis, deformation of skulls, coal-ashes additions, eggshell in the burials, and so on) are fixed. Among the funeral objects the things, peculiar to the Sarmatian relics (moulded pottery, bells...) as well as to the North-Western territories (Cherniakhov wheel-made bi-conoidal shaped vessels, incaved garter-fibulas, bone-made comb, bronze axe-like, and amber mushroom-like pendants) are met.
The presence of such slab burials with the same burial rite and accessories in the necropolises of the Roman time in the different regions of South-Eastern Europe gives grounds to the suggestion about the penetration of the North Caucasian aboriginals, who bore the Sarmatian influences, together with the other Sarmato-Alanian tribes into the Northern Black Sea area. The Sarmatian presence on the territory of Ukraine in the first centuries AD confirms their presence in the composition of the bearers of Chernyakhovskaya culture.